Are Oil Prices Mean Reverting? Evidence from Unit Root Tests with Sharp and Smooth Breaks - Lawal, Adedoyin Isola; Babajide, Abiola A.; Nwanji, Tony Ikechukwu; Eluyela, Damilola (International Journal of Energy Economics and Policy, 2018)
This study examined the validity of efficiency market hypothesis for the oil market by employing a novel Fourier unit root test that accounts for sharp shifts and smooth breaks based on daily data. Our results established the existence of structural shifts and nonlinearity in the oil market indices suggesting that oil market is inefficient when structural breaks is calibrated into the model. Unlike results obtained from existing traditional unit root test, results from sharp shifts and smooth breaks unit root test suggests the rejection of unit root null for each of the oil indices. The study has some practical and policy implications based on our findings. Keywords: Oil prices; Market Efficiency; Fourier analysis; Unit root tests; Energy. JEL Classifications: C22, C50, G10, G12 DOI: https://doi.org/10.32479/ijeep.6980